Natural resources and agriculture: A study in the city of Balsas from the rural environmental registry data (Research, Society and Development, 2021)
The Rural Environmental Registry (CAR) is a mandatory electronic record for all Brazilian rural properties, this record is intended to monitor and inspect natural resources mainly related to vegetation and water resources. The data is available for download on public websites. This work used the CAR data to analyze the environmental situation of the municipality of Balsas in the south of Maranhão, having as classes of analysis the preserved vegetation, the rural properties and the registered springs. The methodology applied in the work was partly built by EMBRAPA, and allowed to present the data of the municipality in a mapped, quantified and qualified way. The municipality of Balsas has a total of 2,272 registered properties, contains 39.5% of its preserved vegetation and a total of 345 springs. From the results of this research, it can be inferred that the municipality complies with the requirements of environmental legislation.